ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN PENERAPAN METODE FULL COSTING PADA UMKM KOTA BANDA ACEH - Mifta Maghfirah; Fazli Syam BZ (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
Calculation and acquisition cost of production is strongly Influenced by the application of the method right, so the cost of production is obtained to indicate the actual value occurs. This study conducted on Banda Aceh micro, small and medium enterprises, especially processing businesses of tofu. The purpose of this study is to analyze the production cost price calculation and allocation of costs applied by Banda Aceh micro, small and medium enterprises with the calculation the cost of production using the full costing method. The type of data used in this study is qualitative data which presented in a descriptive or shape description, and quantitative data is presented in the numbers. Sources of data derived from primary data results of interviews conducted with business owners tofu in Banda Aceh, and secondary data obtained from the literature review and other literature that supports the writing of this study. The results indicate that the acquisition cost of production using the full costing method is better in analyzing production costs, its caused the calculation cost of production using the full costing method has included all overhead costs, both fixed and variable during the production process.Keywords— Cost of Production, Full Costing, Process Cost